Navigating C++ and object-oriented design - Anderson, Paul 1949-; Anderson, Gail 1951- (Prentice Hall PTR, 1997)
Navigating C++ and Object-Oriented Design is the first book that teaches ANSI C++ and the object-oriented techniques that make C++ a software development breakthrough. This comprehensive tutorial reflects the authors' extensive experience teaching C++ to professional developers. Start with the clearest introduction to object modeling, then learn all the essentials of C++ and more advanced topics such as exceptions, namespaces, and dynamic memory allocation. Discover C++ classes, the basic building block of object-oriented design. Through proven analogies and examples, the authors introduce containment and inheritance, overloading, templates, RTTI, and exception handling. The unique presentation on multiple inheritance will give readers invaluable insights into this complex topic. Learn to apply C++ and object-oriented techniques to real-world development. Discover how to design classes effectively using the authors' class design boilerplate. Understand how to design container classes. Walk through class designs using the powerful OMT methodology.
Includes index
Keywords: C++ (Computer program language); System design; Object-oriented methods (Computer science); C++ (Langage de programmation); Conception de systèmes; Conception orientée objet (Informatique)